Effect of the Bloomfield program on English as foreign language skills - Lévano Francia, Luz (2021)
The objective of the research carried out was to determine the effect of the Bloomfield program on the competences of English as a foreign language in the students of a language center-2020. The research had an applied study, experimental design and a quasi-experimental class. The sample was non-probabilistic, in which a pre-test and post-test of level A1 were applied within the Common European Framework of References. The total population was 317, and the selected sample of 174 students. The results were tabulated from the collection of test results. Then the results in the post test showed that 100% were at the beginning level, 0% achieved, and 0% outstanding. On the other hand, the post test showed that 0% in the beginning, 1% in the process level, and 99% in the outstanding level in the competence of English as a foreign language. Concluding in this way that the applied program significantly improves the competences of English as a foreign language in Peruvian students in Bloomfield Idiomas, 2020.